Research on seismic response of long-span continuous rigid frame bridge in degraded permafrost regions. (14th June 2022) - Li, Jianning; Sun, Xuexian; Li, Ziqi; Lu, Wei
To study the influence of permafrost degradation on seismic response of a bridge, a large-span continuous rigid frame bridge in warm permafrost regions of Qinghai-Tibet Plateau was used as research object, two permafrost degradation modes have been studied, Results showed that permafrost temperature has less influence on seismic response of rigid-framed pier but more obvious on movable pier under the overall warming degradation mode. However, the maximum bending moment of pile decreases and its position move down with temperature rise, while along transverse direction, the position all at top of piles. When under top-bottom degradation mode, only movable pier are significantly affected in longitudinal direction. The maximum bending moment of pile increases and its position move down with degradation depth. In general, the adverse effects caused by permafrost degradation should be considered in piles, but for piers just consider it to a certain extent.